Narrative Skills of Bilingual Children with Autism Spectrum Disorder - Huong Hoang; Ana Maria Gonzalez-Barrero; Aparna Nadig (Discours)
The study investigated how narratives are influenced by both autism spectrum disorder (ASD) and bilingualism. We analyzed the short narratives of school-age Quebec French-speaking children: bilinguals with and without ASD, and monolinguals with and without ASD. Children were given sets of three picture cards depicting a scenario, and were asked to sequence the cards and tell a story. We measured: (1) language production (number of utterances, total number of words), (2) macrostructure (appropriate sequencing of events, number of events mentioned, coherence), (3) microstructure (character introductions, maintenance of referential terms, use of grammatical gender, use of connectives), and (4) evaluative devices (both linguistic and non-linguistic), and mental state terms. With respect to language production, bilinguals produced more utterances than monolinguals, despite having marginally lower receptive vocabulary scores in French. With respect to macrostructure, typically-developing children provided more coherent narratives. No significant differences were found on microstructure or evaluative devices, but evaluative devices were infrequent for all groups. There were no decrements in the narratives of bilingual children relative to monolingual children, both with and without ASD; in fact we found an increased number of utterances in the narratives of bilinguals. The current findings suggest that bilingualism does not negatively affect narrative skills in children with ASD.